Examination of The BBC's Approach to Managing Ethics and The Implications for A Future Code of Ethics - Bowett, Natascha Karen (2005)
This study attempts to draw on academic literature surrounding the media and business ethics to examine ethical issues, the management of those issues and the implications of a code of ethics for a media organisation like the BBC. Qualitative interviewing was used to provide the research data to compare and contrast with the literature discussed.